Prediksi Performa Mahasiswa Menggunakan Model Regresi Logistik - Nurmalitasari Nurmalitasari; Eko Purwanto (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
Prediction of student performance is an important thing for a university. This is because it can help a university to prevent or treat students who are at risk of failing in their studies early. This study aims to predict student performance at Duta Bangsa Surakarta University (UDB). The model used in this study is a logistic regression model. Logistic regression is a mathematical modelling method used to determine the relationship between a binary dependent variable and one or more independent variables. The results showed that the logistic regression model could be used to predict student performance with MAPE by 8%. Keyword: Student Performace, Logistic Regression, UDB, MAPE